The effect of AMF suppression on plant species composition in a nutrient-poor dry grassland - Dostálek, Tomáš; Pánková, Hana; Münzbergová, Zuzana; Rydlová, Jana (PloS one, 2013)
Arbuscular mycorrhizal fungi (AMF) are expected to be one of the key drivers determining the diversity of natural plant communities, especially in nutrient-poor and dry habitats. Several previous studies have explored the importance of AMF for the composition of plant communities in various types of habitats. Surprisingly, studies of the role of AMF in nutrient-poor dry grassland communities dominated by less mycotrophic plant species are still relatively rare. We present the results of a 3-year study in which a plant community in a species-rich dry grassland was subjected to the fungicide carbendazim to suppress AMF colonization. We tested the effect of the fungicide on the following parameters: the plant species composition; the number of plant species; the cover of the rare, highly mycorrhiza-dependent species Aster amellus; the cover of the dominant, less mycorrhiza-dependent species Brachypodium pinnatum; and the cover of graminoids and perennial forbs. In addition, we examined the mycorrhizal inoculation potential of the soil. We found that the suppression of AMF with fungicide resulted in substantial changes in plant species composition and significant decrease in species richness, the cover of A. amellus and the cover of perennial forbs. In contrast the species increasing their cover after fungicide application were graminoids--the C3 grasses B. pinnatum and Bromus erectus and the sedge Carex flacca. These species appear to be less mycorrhiza dependent. Moreover, due to their clonal growth and efficient nutrient usage, they are, most likely, better competitors than perennial forbs under fungicide application. Our results thus suggest that AMF are an essential part of the soil communities supporting a high diversity of plant species in species-rich dry grasslands in nutrient-poor habitats. The AMF are especially important for the maintenance of the populations of perennial forbs, many of which are rare and endangered in the area.
Keywords: biodiverzita; houby; Droughts; období sucha; fyziologie rostlin; rostliny; mykorhiza; Poaceae; Fungi; Mycorrhizae; lipnicovité; Plant Physiological Phenomena; Biodiversity; Fungicides, Industrial; Plants; ekosystém; Ecosystem; Soil; průmyslové fungicidy; půda